PERANCANGAN E-LEARNING SMA DAMAI PADA PLATFORM ANDROID DAN WEBSITE - Edwin Suryaputra; Bagus Mulyawan; Novario Jaya Perdana (Fakultas Teknologi Informasi Universitas Tarumanagara, 2019)
During this time DAMAI High School still applied a conventional system in the teaching and learning process conducted by teachers with students. Therefore, the solution needed is to make an Android-based e-learning application and website. E-Learning is a system or concept of education that utilizes information technology in the teaching and learning process. This e-learning application is made using descriptive research methods with a type of case study research in schools, where data collection techniques are used between observation and interviews. For the development method using a structured method with several tools and workmanship techniques such as flowcharts, context diagrams, and relationships between tables. The programming language used in designing e-learning is PHP and the database used is MySQL. The method used to integrate Android with a website is by using a RESTful API that is distributed using JSON. With the DAMAI high school e-learning Android and website application solution, it is hoped that it can help teachers and students in conducting teaching and learning activities flexibly.